Typical Fish Protein and Fish Waste - Haetami, Kiki; Aditia, Aditia; Dhiyaulhaq, Azmi; Abun, Abun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Fishery waste such as offal, skin, and bones still contains high-value protein that has the potential to be processed into protein hydrolysates and gelatin. This study aims to analyze the utilization of fish waste and its biochemical changes during storage. The method used was a descriptive literature review. The results show that protein hydrolysis produces bioactive peptides with antioxidant activity. Furthermore, the formation of natural formaldehyde in fish occurs due to the degradation of TMAO by enzymes, which persists at low temperatures. The use of natural ingredients as preservatives can slow down deterioration, while pH sensor technology can help visually monitor fish freshness. Utilizing fish waste and implementing supporting technologies is a strategic step in increasing the added value and quality of fishery products.